KRITIK ATAS SIKAP TANPA PAMRIH (DISINTERESTED ATTITUDE) MELALUI SUDUT PANDANG VOYEURISTIK - Richardo Torang Manahan; Harsawibawa Albertus (LPPM Institut Pendidikan Nusantara Global, 2023)
A work of art contains a stratified aesthetic element in accordance with the satisfaction of the human senses. Beauty is often directed at the object of the human body which is displayed tabooly in the form of